1953
DOI: 10.1017/s0022029900006786
|View full text |Cite
|
Sign up to set email alerts
|

506. The importance of machine milking rate in dairy cow management and breeding

Abstract: With 2 Figures)The discoveries of the last decade have considerably improved our understanding of the neural and hormonal mechanisms controlling milk ejection. This, in turn, has stimulated research into the many practical problems concerned with hand and machine milking. The discovery that milk ejection is a transitory mechanism encouraged the study of the rate of machine milking of dairy cows since it was inferred that less milk is obtained when milking is slow. This research work has shown that there are ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

1953
1953
1976
1976

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 9 publications
3
17
0
Order By: Relevance
“…The weighted mean regression coefficient calculated on the complete data is very highly significant. This direct relationship between inherent milking rate and yield in the first lactation confirms the earlier results (2).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The weighted mean regression coefficient calculated on the complete data is very highly significant. This direct relationship between inherent milking rate and yield in the first lactation confirms the earlier results (2).…”
Section: Resultssupporting
confidence: 90%
“…In practice, involuntary culling on the basis of milking rate will occur even when its direct measurement is not made (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for all the determinations measured the overall changes between the first lactation group and the oldest lactation group are significant at either the 5 or 1 % level. Elsewhere (12) we have shown that in this herd the lactation age at culling is related to milking rate in such a way that slow milkers are culled at an earlier age than fast milkers. Thus the figures in Table 8 do not give a true measure of the effect of age on milking rate.…”
Section: Lactation Agementioning
confidence: 68%
“…The rate of milking, as one of the major factors determining the total time of machine-milking (Donald, 1960), has received considerable attention in the herd of the National Institute for Research in Dairying (Dodd and Foot, 1953;Dodd, 1953;Clough and Dodd, 1957). The rate of milking, as one of the major factors determining the total time of machine-milking (Donald, 1960), has received considerable attention in the herd of the National Institute for Research in Dairying (Dodd and Foot, 1953;Dodd, 1953;Clough and Dodd, 1957).…”
mentioning
confidence: 99%